Psychological aspects of effective strategic partnership management - V. I. Dobrosotskij; A. N. Zankovskii (Управление, 2020)
Strategic partnerships that were formed since the end of the last century, as effective business elements of integration of the economic world, are now the most promising form of business development. They allow us to overcome the negative aspects of forced growth and consolidation, leave partners room to choose the best solutions, focus on the future, and increase the stability of partner companies in providing resources and distributing products and services. Today, such partnerships have become an important tool of competition, opening up opportunities to enter new markets. According to the structure, a strategic partnership can combine numerous organizational forms, including joint ventures, license agreements, long-term contracts for the supply and purchase of products, j oint research and development programs, and mutual provision of implementation networks. Strategic partnership management is a very complex, specific activity and area of corporate management in which it is extremely important to maintain a balance between the interests of the alliance as a whole, the interests of the company and the interests of the partner company, taking into account the interests of shareholders, strategic investors and other interested parties.Specific examples of strategic alliances, the dynamics of their development, and the reasons for their success or failure have been considered in the article. It has been demonstrated that a serious obstacle to effective corporate cooperation has mainly psychological than economic reasons. The concept of the psychological syndrome of strategic partnership has been proposed, its content and structure, including individual, organizational and cultural components, have been revealed. The ways to overcome this syndrome, including the creation and training of a strategic partnership team, have been briefly outlined. For a detailed description and evaluation of the effectiveness of the proposed psychotechnology of organizational development, a separate article will be required, which we plan to present in one of the next issues.